Magnetite-coated metal foams as one-body catalysts for Fenton-like reactions - Thi May Do; Byun, Ji Young; Kim, Sang Hoon (SPRINGER, 2017)
The possibility of preparing one-body catalyst was investigated for heterogeneous Fenton-like reactions by coating magnetite powder on metal foams. Up to 10 wt% magnetite could be coated onto metal foams with strong enough adhesion. The catalytic efficiency of the catalyst was investigated using a model reaction of methylene blue degradation at a circumneutral pH using H2O2 as the source of OH radicals and oxalic acid as the chelating agent. Comparison with conventional magnetite powder indicated that the catalytic efficiency of magnetite-coated metal foam was better than that of the powder only due to a larger exposed surface area. After treatment, separation of the one-body catalyst was easier and cleaner than that of conventional magnetite powder catalyst.
Keywords: OXIDATION; NANOPARTICLES; KINETICS